Survey Tingkat Kebugaran Jasmani Mahasiswa PJKR UMMI Semester 5 Angkatan 2019 - Bachtiar Bachtiar; Salsa Najwa Aulia; Hilda Nuraeni (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This study aims to determine the level of physical fitness of PJKR FKIP students, Muhammadiyah University of Sukabumi. The method used to collect data to determine the ability to take maximal oxygen (V02 Max) by means of tests and measurements, namely the multistage fitness test. The sample used in this study were PJKR force2019 students, totaling 23 people. The data analysis technique in this study uses percentage analysis. The results showed that of 23 PJKR students. there are 4 students or 17.3% have very low V02 Max ability, 5 students or 21.7%, 9 students or 39.1% have moderate V02 Max ability, 5 students or 21.7% in good category and there are no PJKR students which has a very good V02 max capability. From these results, it can be concluded from this research that the physical fitness level of the 2019 PJKR students is in the moderate category or around 39.1% of the 23 total students.